Relationship between Knowledge and Compliance Using Anti-dyslipidemic Drugs among Hypertensive Patients with Dyslipidemia in Bandung, West Java, Indonesia - Batasalsabilla, Sitti Alifa; Kuswinarti, Kuswinarti; Andean, Rudolf (Althea Medical Journal, 2024)
Background: Dyslipidemia occurs in 60% of hypertensive patients. Effective treatment of hypertensive patients with dyslipidemia can reduce the risk of cardiovascular disease by more than 50%. However, compliance with dyslipidemia medication in dyslipidemia patients is still low. Low compliance can be attributed to poor knowledge. This study aimed to analyze the relationship between knowledge and compliance using antidyslipidemic drugs in hypertensive patients with dyslipidemia.Methods:  A cross-sectional analytical study was conducted from August to September 2022 at the Pasirkaliki Public Health Center (Pusat Kesehatan Masyarakat, Puskesmas), Bandung, Indonesia. The consecutive sampling method was used to collect 64 hypertensive patients with dyslipidemia who were taking anti-dyslipidemic drugs. Primary data on knowledge and compliance were obtained through valid and reliable questionnaires. The Chi-square test was used to determine the relationship between the two variables.Results: The study results showed that 95.3% of respondents had good knowledge. Respondent compliance showed obedience of 78.1%. Respondents with good knowledge had an obedience rate of 78.1%. There was a relationship between knowledge and compliance to using anti-dyslipidemic drugs in hypertensive patients with dyslipidemia (p=0.001).Conclusions: There is a relationship between knowledge and compliance with the use of anti-dyslipidemia drugs in hypertensive patients with dyslipidemia. Almost all patients have good knowledge.  Continuous maintenance and improvement of patient knowledge is required, which can be achieved by conducting health education to better understand the relationship between diseases and the importance of taking medication.